Prompt Engineering Using ChatGPT - Crafting Effective Interactions and Building GPT Apps - Tabatabaian, Mehrzad (MLI Generative AI Series, 2024)
This book is designed for mastering the art and science of prompt engineering in the realm of artificial intelligence. It provides a thorough exploration of the fundamental principles, practical techniques, and real-world applications of prompt engineering, with a special focus on ChatGPT and its advanced iterations, including GPT-4 and GPT plug-ins. You will learn the essential role of prompts in interacting with ChatGPT, understand the anatomy of a well-constructed prompt, and explore different prompt styles. The book also shows how to set constraints and guidelines to steer AI responses toward desired outcomes and ensure ethical and responsible interactions. Whether you're a novice of generative AI or seeking advanced insights, this book is your companion for mastering prompt engineering and building innovative GPT applications. FEATURES:Discusses the fundamental groundwork for understanding prompts, their role in guiding AI models, and their impact on the quality of generated responsesProvides real-world applications demonstrating how prompt engineering is applied across various domains, from customer support and education to business and technical fieldsIncludes a chapter on GPT-4 Plugins showing how to extend the capabilities of GPT-4 and create more versatile AI-powered applicationsDescribes techniques for formulating clear and direct questions to obtain precise answers from AI models